The role of hindrance stressor and distress in teachers’ work-life balance - Pan, Lee Ching; Chua, Bee Seok; Rosnah Ismail (Atlantis Press, 2021)
Excessive workload is appraised as hindrance stressor because it obstructs teachers' achievement in the workplace and then to a negative response like distress, the response would harm the work-life balance. Hence, this study aims to examine the relationship between hindrance stressor and work-life balance through the mediation role of distress. Through a survey, 491 valid questionnaires were collected from public secondary school teachers in Sabah. Challenge-hindrance Appraisal Scale was used to analyse hindrance stressor, Stress Professional Positive and Negative Questionnaire measured distress, and Survey Work-home Interaction-Nijmegan scaled work-life balance. Partial Least Square-Structural Equation Modeling (PLS-SEM) was used to test hypotheses. The result showed the indirect effect of hindrance stressor on work-life balance through the mediation role of distress was significant. A high level of hindrance stressor increases distress, in turn, lead to negative interaction, decrease positive interaction between work and life. These findings could empower education stakeholders to acknowledge excessive workload obstruct positive interaction between work and life. This study implies control workload proportion is essential that may ultimately improve work-life balance.